Privacy preserving knowledge graph for healthcare applications. Issue 1 (1st September 2022) - Sharma, N; Bhatt, R
Abstract: Knowledge graphs in healthcare applications help all the stakeholders in the healthcare domain. The doctors can consult across various hospitals for a particular scenario or can query the knowledge graph for the history of the patients. Similarly, the patients can query the knowledge graph through well-defined interface or a Chabot system for location of the nearest doctor with a high rating. The physicians can query the knowledge graph for a generic drug family or detecting salt of a particular drug. The paper proposes architecture for knowledge graph in healthcare domain. Further, privacy preserving for a medical domain is an essential requirement. The paper proposes privacy preserving schemes for knowledge graph for healthcare applications.